Giant planets around AF and M stars. Issue Volume 8:Issue S299(2013) (6th January 2014) - Rameau, Julien; Chauvin, Gaël; Lagrange, Anne-Marie; Delorme, Philippe; Lannier, Justine
Abstract: We present the results of two three-year surveys of young and nearby stars to search for wide orbit giant planets. On the one hand, we focus on early-type and massive, namely β Pictoris analogs. On the other hand, we observe late type and very low mass stars, i.e., M dwarfs. We report individual detections of new planetary mass objects. According to our deep detection performances, we derive the observed frequency of giant planets between these two classes of parent stars. We find frequency between 6 to 12% but we are not able to assess a/no correlation with the host-mass.